Applied Mathematical Problems in Engineering - Carlos Llopis-Albert; Daniel Palacios-Marques (Multidisciplinary Journal for Education, Social and Technological Sciences)
There is a close relationship between engineering and mathematics, which has led to the development of new techniques in recent years. Likewise the developments in technology and computers have led to new ways of teaching mathematics for engineering students and the use of modern techniques and methods.  This research aims to provide insight on how to deal with mathematical problems for engineering students. This is performed by means of a fuzzy set/Qualitative Comparative Analysis applied to conflict resolution of Public Participation Projects in support to the EU Water Framework Directive.